Spatial clusters and temporal trends of seasonal surface soil moisture across China in responses to regional climate and land cover changes. Issue 2 (26th January 2017) - Chen, Xiuzhi; Liu, Xiaodong; Liu, Zhiyong; Zhou, Ping; Zhou, Guoyi; Liao, Jishan; Liu, Liyang
Abstract: Investigating the spatiotemporal changes of regional surface soil moisture in responses to climate and land cover changes is vital for understanding the underlying mechanisms of hydrological processes. While previous studies mainly attributed the causes of soil moisture changes to climatic factors, few took land cover into consideration. We analyzed the seasonal‐differentiated effects of climate and land cover changes on surface soil moisture of China's 80 drainage basins using the Essential Climate Variable Soil Moisture product spanning the 1979–2010 period. The low–low spatial clusters of annual (Jan–Dec), warm‐season (Apr–Sept) and cool‐season (Oct–Dec and Jan–Mar) surface soil moisture have spread from Northwest China to northeast and even Central China during the past three decades. In cool seasons, significant decreasing trends of surface soil moisture in most drainage basins of Northwest, Northeast, Central, and South China were detected. But in warm seasons, the surface soil moisture in Central and South China showed significant increasing trends. Precipitation, potential evapotranspiration and the ratio of the two are three driving forces for warm‐season surface soil moisture changes in Northeast and Northwest China. These climatic factors are main contributors to the declining trends of cool‐season surface soil moisture in Central and South China. Land cover changes showed to be the major factor driving the significant decreasing trends of cool‐season surface soil moisture in Northwest, Central, and South China. Due to vegetation's self‐shading effect, the large‐scale reforestation and vegetation growth are believed as main causes of the increasing trends of warm‐season surface soil moisture in Central and South China.